Distribution maps of vegetation alliances in Europe. Issue 1 (8th March 2022) - Preislerová, Zdenka; Jiménez‐Alfaro, Borja; Mucina, Ladislav; Berg, Christian; Bonari, Gianmaria; Kuzemko, Anna; Landucci, Flavia; Marcenò, Corrado; Monteiro‐Henriques, Tiago; Novák, Pavel; Vynokurov, Denys; Bergmeier, Erwin; et al.
Abstract: Aim: The first comprehensive checklist of European phytosociological alliances, orders and classes (EuroVegChecklist) was published by Mucina et al. (2016, Applied Vegetation Science, 19 (Suppl. 1), 3–264). However, this checklist did not contain detailed information on the distribution of individual vegetation types. Here we provide the first maps of all alliances in Europe. Location: Europe, Greenland, Canary Islands, Madeira, Azores, Cyprus and the Caucasus countries. Methods: We collected data on the occurrence of phytosociological alliances in European countries and regions from literature and vegetation‐plot databases. We interpreted and complemented these data using the expert knowledge of an international team of vegetation scientists and matched all the previously reported alliance names and concepts with those of the EuroVegChecklist. We then mapped the occurrence of the EuroVegChecklist alliances in 82 territorial units corresponding to countries, large islands, archipelagos and peninsulas. We subdivided the mainland parts of large or biogeographically heterogeneous countries based on the European biogeographical regions. Specialized alliances of coastal habitats were mapped only for the coastal section of each territorial unit. Results: Distribution maps were prepared for 1, 105 alliances of vascular‐plant dominated vegetation reported in the EuroVegChecklist. For each territorial unit, three levels of occurrence probability were plotted on the maps: (a) verified occurrence; (b) uncertain occurrence; and (c) absence. The maps of individual alliances were complemented by summary maps of the number of alliances and the alliance–area relationship. Distribution data are also provided in a spreadsheet. Conclusions: The new map series represents the first attempt to characterize the distribution of all vegetation types at the alliance level across Europe. There are still many knowledge gaps, partly due to a lack of data for some regions and partly due to uncertainties in the definition of some alliances. The maps presented here provide a basis for future research aimed at filling these gaps. Abstract : We provide distribution maps for 1, 105 phytosociological alliances of vascular‐plant dominated vegetation listed in the EuroVegChecklist. The alliances were mapped in 82 territorial units, in which three levels of occurrence probability are indicated: (a) verified occurrence; (b) uncertain occurrence; and (c) absence. We also provide summaries showing the number of alliances in different European regions.